Pengaruh Kinerja Keuangan terhadap Pertumbuhan Laba pada Perusahaan Telekomunikasi yang Terdaftar di ISSI Periode 2020 – 2023 - Belva Syafiatul Fitra (Akubis : Jurnal Akuntansi dan Bisnis, 2025)
The increasingly rapid development of the Indonesian business world has driven companies to increase their competitiveness. Companies strive to continuously innovate their businesses to improve their performance and survive amidst intense competition. The fundamental purpose of establishing a company is to maximize profits, one of which is by maximizing its performance. This study aims to uncover the impact of financial performance on profit growth in telecommunications companies registered with the Indonesian Stock Exchange (ISSI) between 2020 and 2023. The data used in this study are secondary. The sample size was eight companies, using purposive sampling. The method used was quantitative. The data analysis techniques used were descriptive statistics, panel data regression analysis, classical assumption testing, and hypothesis testing, assisted by eViews-12. The results of the study revealed that partially, the current ratio had a negative but insignificant effect on profit growth, the debt-to-equity ratio had a negative but significant effect on profit growth, and the net profit margin had a negative but insignificant effect on profit growth. Simultaneous testing revealed that the current ratio, debt-to-equity ratio, and net profit margin had a significant effect on profit growth.